Correction to: A common arthropod from the Late Ordovician Big Hill Lagerstätte (Michigan) reveals an unexpected ecological diversity within Chasmataspidida - James C. Lamsdell; Gerald O. Gunderson; Ronald C. Meyer (BMC Ecology and Evolution, 2021)
An amendment to this paper has been published and can be accessed via the original article.